1988
DOI: 10.4315/0362-028x-51.6.445
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Examination of Yersinia enterocolitica Attached to Stainless Steel at Selected Temperatures and pH values

Abstract: Attachment of Yersinia enterocolitica to stainless steel surfaces at 35, 21, and 10°C was investigated using scanning electron microscopy (SEM). Cells adhered at all three temperatures, but, in general, the greatest number of adhered cells were observed at pH 8 and 21°C. Multi-flagellated cells were noted under these growth conditions. When grown at pH 9.5 and 21°C, fibrils were observed between cells and extending to the stainless steel surface. Fewer cells with flagella were seen at this pH. Adherence may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 0 publications
0
24
0
1
Order By: Relevance
“…Some previous studies have reported a positive effect of lower temperature on the adhesion pattern of S. aureus. Herald and Zottola (1988) noted that Listeria monocytogenes and Yersinia enterocolitica cultivated in laboratorial media adhered to stainless surfaces in greater numbers at 21 ºC than at 30 ºC. Rode et al (2007) found higher attachment capacity for S. aureus on polystyrene when cultivated in tryptic soy broth at sub-optimal temperatures (20, 25 and 30 ºC).…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have reported a positive effect of lower temperature on the adhesion pattern of S. aureus. Herald and Zottola (1988) noted that Listeria monocytogenes and Yersinia enterocolitica cultivated in laboratorial media adhered to stainless surfaces in greater numbers at 21 ºC than at 30 ºC. Rode et al (2007) found higher attachment capacity for S. aureus on polystyrene when cultivated in tryptic soy broth at sub-optimal temperatures (20, 25 and 30 ºC).…”
Section: Resultsmentioning
confidence: 99%
“…Adhesion phenomena has been evaluated as function of substratum, liquid medium, carbone source, pH and hydrodynamics parameters including flow rate. Many of the conclusions about biofilm development, composition, distribution, and relationship to substratum have been derived from scanning electron microscopy (Bragadeewaran et al, 2010;Herald & Zottola, 1988;Pinna et al, 2000). We report here several investigations made in our laboratory used scanning electron microscopy to study adhesion phenomena.…”
Section: Sem Applied Of Adhesion Stagementioning
confidence: 89%
“…Pseudomonas aeruginosa and Listeria monocytogenes cells show the maximal adhesion on abiotic materials at neutral pH and a temperature of 30ºC [Herald & Zottola, 1988a;Busalmen & de Sanchez, 2001]. In Yersinia enterocolitica the adhesion is enhanced on solid surfaces at pH 8-9 and a temperature of 30ºC [Herald & Zottola, 1988b].…”
Section: Other Factorsmentioning
confidence: 93%